Dynamics of K^th Order Rational Difference Equation
In this paper we will investigate the dynamical behavior of the following rational difference equation x_n+1= α + β x_n + γ x_n-k A +B x_n + C x_n-k ,n=0,1,... 1 where the parameters α, β, γ and A, B, C and the initial conditions x_-k,…,x_-1,x_0 are non-negative real numbers, and the denominator is nonzero. Our concentration here, is on the global stability, the periodic character, the analysis of semi-cycles and the invariant intervals of the positive solution of the above equation. It is worth mentioning that our difference equation is the general case of the rational equation which is studied by Kulenovic and Ladas in their monograph ( Dynamics of Second Order Rational Difference Equation with Open Problems and Conjectures, 2002 )., number=1, journal=Journal of Applied Nonlinear Dynamics, author=Saleh, Mohammad and Asad, A., year=2026, month=Aug., pages=125–149